Guidelines on restructuring enterprises - Garškaitė-Milvydienė, Kristina (Business: Theory and Practice, 2013)
The paper discusses the general principles of restructuring enterprises, submits various interpretations of the concept „restructuring“ and states the content and activities of restructuring enterprises. Restructuring enterprises can be implemented according to certain stages. When negative tendencies for the activity of the enterprise become visible or the current economic and financial indices become unsatisfactory, the issue about a further possibility of proceeding with the activity of the enterprise is considered. Seeking for restructuring the enterprise, first, the expediency and possibilities of the actions taken must be well-grounded. Then, the conception of restructuring and directions for implementing it are fixed; they stipulate the selection of the form of restructuring the enterprise (anti-crisis management instrument). The selection of restructuring depends upon the chosen form of restructurization. The preparation of a business plan, including appropriate elements, serves as an important stage of restructuring the enterprise. The foreseen results of restructuring are assessed with the help of certain methods seeking for the evaluation of its efficacy. The issued (business) plan of restructuring is approved and implemented. This process must be controlled while implementing the plan of restructuring enterprises.Įmonių restruktūrizavimo gairėsSantraukaStraipsnyje nagrinėjami bendri įmonių restruktūrizavimo principai. pateikiamos įvairios restruktūrizavimo sąvokos interpretacijos, išdėstomas įmonių restruktūrizavimo turinys ir priemonės. Įmonių restruktūrizavimas gali būti įgyvendinamas tam tikrais etapais. Kai įmonė pastebi neigiamas veiklos tendencijas ar kai nepatenkinami einamieji ūkiniai ir finansiniai poreikiai, sprendžiamas  klausimas  dėl  tolesnės  įmonės  veiklos  tęstinumo  galimybės.  Siekiant  įmonę  restruktūrizuoti,  pirmiausia  turi  būti  pagrįstas  restruktūrizavimo  tikslingumas  ir  galimybės.  Toliau  nustatoma  restruktūrizavimo  koncepcija  ir  įgyvendinimo  kryptis,  nuo  kurių  priklauso  pasirenkama  įmonės  restruktūrizavimo  forma  (antikrizinio  valdymo  priemonė).  Nuo  pasirinktos  restruktūrizavimo  formos  priklauso  restruktūrizuotojo  parinkimas.  Svarbus  įmonių  restruktūrizavimo  etapas  –  verslo  plano parengimas, kurį sudaro atitinkami elementai. Numatomi restruktūrizavimo rezultatai įvertinami tam tikrais metodais, apskaičiuojant jo efektyvumą. parengtas restruktūrizavimo (verslo) planas patvirtinamas ir įgyvendinamas. Įgyvendinant įmonių restruktūrizavimo planą, turi būti vykdoma šio proceso kontrolė.Reikšminiai žodžiai: įmonių restruktūrizavimas, principai, etapai, restruktūrizavimo formos, refinansavimas, pertvarkymas, reorganizavimas, verslo planas.